(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
The experimental and quantum chemical study of polyhydridesiloxane (PHS)–C60 composite has shown that sorption on the PHS surface is reversible and does not lead to formation of stable composites. IR spectroscopic and mass-spectrometric data proves the statement.